Social alienation among older adults with cognitive frailty: a latent profile analysis - Songqing Zhao; Weiping Lu; Peng Lu; Li Zhou; Yan He; Yaohuan Sun; Zeen Wang (Frontiers in Public Health, 2026)
Background The rising prevalence of cognitive frailty among older adults necessitates a deeper understanding of its psychosocial consequences. Social alienation, a critical yet understudied dimension, may exhibit significant heterogeneity in this vulnerable population, with distinct subgroups potentially requiring tailored interventions. Elucidating these patterns could inform more targeted geriatric care strategies. Objectives This study aimed to identify latent profiles of social alienation among older adults with cognitive frailty and examine the associations between sociodemographic and clinical factors and profile membership. Methods A multicenter cross-sectional study was conducted from June to September 2025. A convenience sample of 968 older adults with cognitive frailty was recruited from four tertiary hospitals in Jiangsu Province, China. Latent profile analysis and multinomial logistic regression were performed on data collected using the General Alienation Scale, Perceived Social Support Scale, Geriatric Depression Scale, and Barthel Index. Results Four distinct profiles of social alienation were identified: “Social Adaptation” (15.5%), “Mild Alienation” (23.5%), “Moderate Alienation” (26.5%), and “Severe Alienation” (34.5%). Depression was a significant risk factor associated with higher odds of belonging to all alienation profiles, whereas greater daily living abilities and perceived social support were protective. Notably, living with adult children (compared to living with a spouse) was an independent risk factor specifically associated with the “Severe Alienation” profile. Conclusions Social alienation among older adults with cognitive frailty is highly heterogeneous, with a substantial proportion experiencing severe alienation. These findings suggest that routine screening for alienation could be a valuable addition to geriatric nursing assessments. Furthermore, our results provide an empirical foundation for future studies to develop and test targeted interventions, such as physical and psychological support programs for high-risk individuals, and to explore the feasibility of mobilizing peer support from well-adapted groups.